Clinical Manifestations and Management of Inherited Thrombophilia: Retrospective Analysis and Follow-up after Diagnosis of 238 Patients with Congenital Deficiency of Antithrombin III, Protein C, Protein S - De Stefano, V; Leone, G; Mastrangelo, S; Tripodi, A; Rodeghiero, F; Castaman, G; Barbui, T; Finazzi, G; Bizzi, B; Mannucci, P M (Thrombosis and Haemostasis, 1994)
The clinical history of 238 patients with inherited thrombophilia (AT III = 94, PC = 103, PS = 41) was analyzed retrospectively at diagnosis and in the follow-up period after diagnosis. At diagnosis 129 patients (54%) had suffered from thrombosis, with a recurrence rate of 48%. The most frequent onset manifestation was deep vein thrombosis of lower limbs (58%). Thrombotic history started before 40 in 80% of the cases. Forty-nine percent of the venous thromboses were preceded by a triggering event, in most cases pregnancy (17%) and surgery (12%). After diagnosis, follow-up lasted a total of 1,113 pt-years. A policy of short-term prophylaxis during risk situations for all patients and long-term prophylaxis in symptomatic patients failed to prevent venous thrombotic episodes (diagnosed by objective methods) in 4 previously asymptomatic subjects and recurrence in 7 previously symptomatic subjects. After knowledge of the patients’ diagnosis the incidence of venous thrombosis/100 pt-years was reduced as compared before diagnosis as total episodes (onset + recurrencies) (1.0 vs 1.9), onset episodes (0.7 vs 1.3) and recurrent episodes (1.3 vs 4.8), even though the differences were not statistically significant. However most of the venous thromboses occurred at a more advanced age (67% after 40 years) and without any apparent cause (83%), at significant variance with the period preceding the diagnosis; in particular the incidence of venous thrombotic onset in patients younger than 40 passed from 1.3/100 pt-years to 0.2/100 pt-years. In 6 recurrences after diagnosis a poor compliance for antithrombotic treatment was recognized. We conclude that a policy based on knowledge of diagnosis and on the implementation of antithrombotic treatment during risk situations appears to modify the clinical outcome of deficiencies of natural anticoagulants even in the absence of long-term antithrombotic prophylaxis; in particular morbidity of young patients is significantly reduced.